Association Between Maternal Weight Gain in Different Periods of Pregnancy and the Risk of Venous Thromboembolism: A Retrospective Case–Control Study - Wu, Yuelin; Pei, Jindan; Dong, Lingling; Zhou, Zheying; Zhou, Tianfan; Zhao, Xiaobo; Che, Ronghua; Han, Zhimin; Hua, Xiaolin (Frontiers in Endocrinology, 2022)
Background Venous thromboembolism (VTE) remains an important cause of maternal deaths. Little is known about the associations of specific periods of gestational weight gain (GWG) with category of VTE, pulmonary embolism (PE) or deep venous thrombosis (DVT) with or without PE. Methods In a retrospective case-control study conducted in Shanghai First Maternity and Infant Hospital from January 1st, 2017 to September 30th, 2021, cases of VTE within pregnancy or the first 6 postnatal weeks were identified. Controls without VTE were randomly selected from women giving birth on the same day as the cases, with 10 controls matched to each case. Total gestational weight gain (GWG) and rates of early, mid and late GWG values were standardized into z-scores, stratified by pre-pregnant body mass index (BMI). The adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were estimated through multivariate logistic regression models. Results There were 196 cases (14.4 per 10000) of VTE within pregnancy or the first 6 postnatal weeks were identified. Higher total weight gain was associated with increased risks of PE (aOR, 13.22; 95% CI, 2.03– 85.99) and VTE (OR, 10.49; 95% CI, 1.82–60.45) among women with underweight. In addition, higher total weight gain was associated with increased risk of PE (aOR, 2.06; 95% CI, 1.14-3.72) among women with healthy weight. Similarly, rate of higher early weight gain was associated with significantly increased risk for PE (aOR, 2.15; 95% CI, 1.05-4.42) among women with healthy BMI. Lower rate of late weight gain was associated with increased risks of PE (aOR, 7.30; 95% CI, 1.14-46.55) and VTE (OR, 7.54; 95% CI, 1.20-47.57) among women with underweight. No significant associations between maternal rate of mid GWG and increased risk for any category of VTE, PE or DVT with or without PE were present, regardless of maternal pre-pregnant BMI. Conclusion The GWG associations with category of VTE, PE or DVT with or without PE differ at different periods of pregnancy. In order to effectively improve maternal and child outcomes, intensive weight management that continues through pregnancy may be indispensable.